Upaya Meningkatkan Kreativitas Anak Dalam Pembelajaran Seni Tari Melalui Strategi Belajar Sambil Bermain di TK Islam Sa’adatul Khidmah Tahun Pelajaran 2016/2017 - Miskawati Miskawati (Jurnal Ilmiah Dikdaya, 2019)
This study aims to improve children's creativity in learning dance through learning strategies while playing in Sa'adatul Khidmah Islamic Kindergarten in Jambi City. This study is a classroom action research. The design of this study refers to the Kemmis and Mc Taggart models, covering planning, implementation, observation, and reflection. The subjects of this study were children in group B, Islamic Kindergarten Sa'adatul Khidmah Kota Jambi, which amounted to 16 children, consisting of 8 boys and 8 girls. The collaborator of this research is the Sa'adatul Khidmah Islamic Kindergarten Dance Teacher in Jambi City. The data collection technique used is observation. The research instruments are observation sheets and diaries. The data analysis technique used is descriptive analysis both quantitative and qualitative. The results of the study show that children's creativity can be improved after being given action through play-learning strategies that are applied to dance learning. The results of the observation before the action showed that the average score of creativity obtained by the child was 57.9. There are two aspects of undeveloped creativity, namely originality and elaboration. In the first cycle the average score of creativity increased to 85.83 and all aspects of creativity have developed but there are two aspects whose development has not been optimal, namely flexibility and elaboration. In the second cycle the score of creativity increased to 96.66 on average and all aspects of creativity had grown optimally. The implication of this study is that the teacher will implement a learning strategy while playing to improve children's creativity in dance learning.